Tinjauan Hukum Dan Peran Pemerintah Dalam Tindak Pidana Perdagangan Orang (TPPO) di Kabupaten Karimun Dan Kota Batam - Akbar, Dhani; Indrawan, Indrawan (Jurnal Selat, 2018)
Human trafficking can be classified as one of the worst forms of abuse experienced by human history. Number of the case, regional to international levels, show an increasing trend. Therefore, Indonesia as a part of the world community whose citizens are one of the most victims of human trafficking, seeks to enforce the law and maintain the role as a form of preventive action against the outbreak of Human Trafficking. Local government which is directly contacted with the issue of human trafficking should have strategy to solve the problem. The concept of sustainability fulfillment of security, roles and functions of continuous supervision by local governments is an integral part of the Indonesian constitution, the weakness of the role and supervision of strategy of local government, will increase the problem of social and law. Therefore, there must be joint efforts with other countries. Thus, inter-governmental cooperation, inter-NGO, mass organizations and individuals which are well developed and the synchronization of policy become imperative. Whereas for eradication measures a repressive effort is conducted through coordination among law enforcers which are part of integrated criminal justice system. This is in order to the realization of law enforcement.